The Socio-Economic Prospects for the Anglophone Eastern Caribbean in the Short and Medium Term - Duncan, Neville (UNICEF CAO, 1997)
This paper highlights the fact that the selected evidence presented so far on Eastern and Southern Caribbean economies and poverty indicates a high degree of vulnerability and, in some cases, unsustainably good fortune. A necessary transition to a new economic foundations and the adoption of a new development paradigm is indicated. There is the necessity for a social safety net for the abject poor and dependent populations. New problems are manifesting themselves as stabilizing and adjustment policies take effect—increase in criminal activities, including the illegal drug transshipment trade and the growing domestic use of narcotics, and inadequate waste management, land use practices, and marine management.
Keywords: Social development